A bespoke data linkage of an IVF clinical quality registry to population health datasets; methods and performance. (2021) - Chambers, Georgina M; Choi, Stephanie K.Y.; Irvine, Katie; Venetis, Christos; Harris, Katie; Havard, Alys; Norman, Robert J; Lui, Kei; Ledger, William; Jorm, Louisa R
No abstract available